PENINGKATAN SOFTSKILL MAHASISWA PERAWAT MELALUI KEPEMIMPINAN TRANSFORMASIONAL DOSEN DALAM MENGELOLA KELAS DI FIKKES UNIMUS - Tri Hartiti; Ernawati Ernawati (Universitas Muhammadiyah Semarang, 2017)
Background: A nursing lecturer is an individual responsible for learning process management of nursing students who are expected to professionally provide health services (care provider) in the forms of biological, psychological, social, and spiritual services to individuals, families, and communities in the future. A nursing lecturer is expected to have competences as a classroom management leader who gives opportunities for students to properly actualize their emotions, the one who effectively utilizes resources, andwho does not only focus on the working results known as transformational leadership. Transformational leadership is widely acknowledged as one leadership model which improves human resources. Objectives: this research aims to figure out the lecturers’ transformational leadership in classroom management at Nursing and Health Faculty of Muhammadiyah University of Semarang.Methods: This non experimental (descriptive) research is conducted with a survey approach on a population of 24 nursing lecturers fulfilling inclusion criteria.